Uji Kapasitas Udara yang Dihasilkan Kompresor Sentrifugal 3 Stage pada Unit Energy di PT Toba Pulp Lestari - Baretya Novita Br Simanungkalit; Karti Karti (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2023)
The research objects the authors observe in this paper is the large capacity of compressed air in the compressor contained in the energy unit at PT. Toba Pulp Lestari, Tbk which is engaged in the pulp and paper industry. in the process of making paper pulp the machine used requires compressed air. The compressor used at PT. Toba Pulp Lestari, Tbk is a 3-stage centrifugal compressor. The purpose of this study was to determine the capacity of compressed air in a 3-stage centrifugal compressor. We're at stage 1 which is the air input is processed until it reaches the specified capacity, then proceed to stage 2 with the same process and reaches the specified capacity continued at stage 3 then the processed air will reach the specified capacity and is the air output to the receiver tank. The amount of compressed air capacity produced by a 3-stage centrifugal compressor for each level is 5886 Nm3/hr.